Comunicação e relações de trabalho no contexto empresarial: a prática discursiva de um informativo organizacional - JOUBERT, Patrícia de Castro (Universidade Federal do Pará, 2012)
This study belongs to the group of researches which focuses on the relation between language and work, mainly on the modern forms of comunication in organizational environments. From the presupposition that the language activities in that environment have a symbolic dimension, oriented to generate positive and strategic results, we elect to investigate in this study the discursive practice functioning materialized in the bulletin of news Bertillon and the symbolic implicatures of this practice to the work routine of the company.That informative, as well as the company, are part of the ideological context from the Total Quality Discourse, which institutes and justifies what we nowdays call as modern management. For the analysis of the bulletin discursive practice, we observe the production activities, difusion and consumption, trying to understand the discourses and the subjects representations involved in these activities. The investigation is part of the French Discourse Analysis filed and it is developed according to the theoretical notions of the Discursive Practice and the Scenography, proposed by Maingueneau (2008a).